Molecular and cellular mechanisms involved in tissue-specific metabolic modulation by SARS-CoV-2 - Santos, Alef Aragão Carneiro dos; Rodrigues, Luiz Eduardo; Alecrim-Zeza, Amanda Lins; de Araújo Ferreira, Liliane; Trettel, Caio dos Santos; Gimenes, Gabriela Mandú; Silva, Adelson Fernandes da; Sousa-Filho, Celso Pereira Batista; Serdan, Tamires Duarte Afonso; Levada-Pires, Adriana Cristina; Hatanaka, Elaine; Borges, Fernanda Teixeira; et al. (Frontiers in Microbiology, 2022)
Coronavirus disease 2019 (COVID-19) is triggered by the SARS-CoV-2, which is able to infect and cause dysfunction not only in lungs, but also in multiple organs, including central nervous system, skeletal muscle, kidneys, heart, liver, and intestine. Several metabolic disturbances are associated with cell damage or tissue injury, but the mechanisms involved are not yet fully elucidated. Some potential mechanisms involved in the COVID-19-induced tissue dysfunction are proposed, such as : a) High expression and levels of proinflammatory cytokines, including TNF-α IL-6, IL-1β, INF-α and INF-β, increasing the systemic and tissue inflammatory state; b) Induction of oxidative stress due to redox imbalance, resulting in cell injury or death induced by elevated production of reactive oxygen species; and c) Deregulation of the renin-angiotensin-aldosterone system, exacerbating the inflammatory and oxidative stress responses. In this review, we discuss the main metabolic disturbances observed in different target tissues of SARS-CoV-2 and the potential mechanisms involved in these changes associated with the tissue dysfunction.